1984
DOI: 10.1056/nejm198402023100502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulindac and Ibuprofen in Patients with Chronic Glomerular Disease

Abstract: We investigated whether the glomerular synthesis of prostacyclin modulates the renal blood flow and glomerular filtration rate in chronic glomerular disease. The urinary excretion of 6-keto-prostaglandin F1 alpha, a stable breakdown product of prostacyclin, was significantly (P less than 0.01) reduced in 20 women with chronic glomerular disease, as compared with 19 controls, whereas excretion of urinary prostaglandin E2 was unchanged. In 10 patients randomly assigned to one week of treatment with ibuprofen, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
79
2

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(86 citation statements)
references
References 16 publications
5
79
2
Order By: Relevance
“…Ciabattoni et al (1980) have first reported that sulindac may be unique because it does not inhibit renal PG synthesis in normal volunteers and in a patient with Bartter's syndrome as measured by urinary PG excretion. These observations were later confirmed by several studies in normal subjects and in patients with chronic glomerular disease or hypertension (Bunning and Barth 1982;Salvetti et al 1982; Ciabattoni et al 1984; Sedor et al 1984; Puddey et al 1985; Vriesendorp et al 1986a). Recently, however, there are controversial results indicating that sulindac reduces urinary excretion of PGE2 and is not specifically renalsparing both in experimental animals and in healthy subjects or in patients with renal, liver of cardiac diseases (Berg and Talseth 1985;Brater et al 1985; Olanoff et al 1985; Roberts et al 1985;Laf et al 1986).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Ciabattoni et al (1980) have first reported that sulindac may be unique because it does not inhibit renal PG synthesis in normal volunteers and in a patient with Bartter's syndrome as measured by urinary PG excretion. These observations were later confirmed by several studies in normal subjects and in patients with chronic glomerular disease or hypertension (Bunning and Barth 1982;Salvetti et al 1982; Ciabattoni et al 1984; Sedor et al 1984; Puddey et al 1985; Vriesendorp et al 1986a). Recently, however, there are controversial results indicating that sulindac reduces urinary excretion of PGE2 and is not specifically renalsparing both in experimental animals and in healthy subjects or in patients with renal, liver of cardiac diseases (Berg and Talseth 1985;Brater et al 1985; Olanoff et al 1985; Roberts et al 1985;Laf et al 1986).…”
supporting
confidence: 67%
“…Such a dissociation between urinary excretion of PGE2 and changes in creatinine and para-amino hippurate clearance after treatment with an NSAID has been already reported by Ciabattoni et al (1984), in which they found the inverse relation between the reduction of these clearances after ibuprofen and basal excretion of 6-keto-PGE1 but not that of PGE2 in patients with chronic glomerular disease. Since human glomeruli mainly produce PGI2 (Hassid and Dunn 1980), these results indicate that changes in glomerular filtration rate is more linked with vascular or glomerular PGI2 synthesis than medullary PGE2 synthesis which is mostly reflected as urinary excretion of PGE2 (Frolich et al 1975).…”
Section: Discussionmentioning
confidence: 63%
“…[15][16][17] Aspirin, 7 acetaminophen, 5,6 and NSAIDS 18 have each been shown to reduce formation of vasodilator prostaglandins from arachadonic acid. In the setting of volume depletion, PGI 2 and PGE 2 enhance glomerular filtration 15,19 and reduce fractional sodium reabsorption. 20,21 These actions help counterbalance the effects of constriction of the renal vasculature caused by angiotensin II and catecholamines 22 under conditions such as chronic kidney failure.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 These actions help counterbalance the effects of constriction of the renal vasculature caused by angiotensin II and catecholamines 22 under conditions such as chronic kidney failure. 19 In addition, ibuprofen and indomethacin have been shown to preferentially inhibit extrarenal prostaglandin synthesis and to elevate blood pressure 16,17 in part, perhaps, by increasing endothelin-1 production. 23 Two cross-sectional studies in elderly populations suggest a link between NSAID use and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies were devoted to relationships between kidney alterations and the urinary excretion of prostaglandins. 6KPGFj, but not PGE2 was reported to be decreased in patients with renal insufficiency by Ciabattoni et al (1984) and Mistry et al (1986), while Patrono et al (1983) found that the urinary TxB2 was not affected in similar conditions.…”
Section: Discussionmentioning
confidence: 98%